2019
DOI: 10.1177/0269216319854186
|View full text |Cite
|
Sign up to set email alerts
|

Do published patient decision aids for end-of-life care address patients’ decision-making needs? A systematic review and critical appraisal

Abstract: Background: Many decisions are made by patients in their last months of life, creating complex decision-making needs for these individuals. Identifying whether currently existing patient decision aids address the full range of these patient decision-making needs will better inform end-of-life decision support in clinical practice. Aims and design: This systematic review aimed to (a) identify the range of patients’ decision-making needs and (b) assess the extent to which patient decision aids address these need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 80 publications
(231 reference statements)
0
13
0
Order By: Relevance
“…Recent reviews of decision aids for EOL [8,9], however, revealed either a scarcity of tools for this context and or a lack of numeric prognostic information to assist patients and families in genuinely informed treatment decisions. More importantly, patients' personal values and preferences for non-medical aspects of end-of-life care were not generally incorporated [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reviews of decision aids for EOL [8,9], however, revealed either a scarcity of tools for this context and or a lack of numeric prognostic information to assist patients and families in genuinely informed treatment decisions. More importantly, patients' personal values and preferences for non-medical aspects of end-of-life care were not generally incorporated [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of decision aids for EOL [8,9], however, revealed either a scarcity of tools for this context and or a lack of numeric prognostic information to assist patients and families in genuinely informed treatment decisions. More importantly, patients' personal values and preferences for non-medical aspects of end-of-life care were not generally incorporated [8,9]. Previous research on prognostic tools and preferences for disclosure [10,11], have identi ed several aspects illustrating the complexity of decisionmaking near the EOL: full or partial prognostic disclosure may be a clinician's duty but is not welcome by all patients and may best be delivered gradually over several encounters [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such aids also assist health professionals to understand patient values and preferences. 12,13 Patient decision aids help patients make decisions about their health care by providing information about their options as well as allowing them to clarify and express their personal values and preferences about those options. 12,14 Shared decision-making and patient decision aids have been well received by kidney services in Denmark and in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of structured communication tools was to improve care goals to assist EOL decision-making. Findings from 19 studies found that communication tools improved the documentation of goals-of-care discussions and ultimately decisions to withdraw life-sustaining treatments when compared to usual care.Similarly, a systematic review using 22 studies byPhillips et al (2019) aimed to identify patients' decision-making needs and assess the extent to which decision aids addressed these needs. To assess the effectiveness of current decision aids, the International Patient Decision Aid Standards (IPDAS) was used.…”
mentioning
confidence: 99%